Percutaneous coronary intervention in patients with cancer using bare metal stents compared to drug-eluting stents - Ahmed, Talha; Pacha, Homam Moussa; Addoumieh, Antoine; Koutroumpakis, Efstratios; Song, Juhee; Charitakis, Konstantinos; Boudoulas, Konstantinos Dean; Cilingiroglu, Mehmet; Marmagkiolis, Konstantinos; Grines, Cindy; Iliescu, Cezar A. (Frontiers in Cardiovascular Medicine, 2022)
Background: Management of coronary artery disease (CAD) is unique and challenging in cancer patients. Little is known about outcomes of using BMS or DES in these patients. The aim of this study was to compare the outcomes of percutaneous coronary intervention (PCI) in cancer patients who were treated with bare metal stents (BMS) versus drug eluting stents (DES). Methods: We identified cancer patients who underwent PCI using BMS or DES between 2013 and 2020. Outcomes of interest were overall survival (OS) and number of revascularizations. Kaplan-Meier method was used to estimate the survival probability. Multivariate Cox regression models were utilized to compare OS between BMS and DES. Results: We included 346 cancer patients who underwent PCI with median follow-up of 34.1 months (95% CI, 28.4-38.7). Among these, 42 patients were treated with BMS (12.1%) and 304 with DES (87.9%). Age and gender were similar between BMS and DES groups (p = 0.09 and 0.93 respectively). DES use was more frequent in white race while black patients had more BMS (p=0.03). Use of DES was more common in patients presenting with NSTEMI (p=0.03). Median survival was 46 months (95%CI, 34-66). There was no significant difference in number of revascularizations between BMS and DES groups (p=0.43). There was no significant difference in OS between BMS and DES groups in multivariate analysis (p = 0.26). Independent predictors for worse survival included age > 65 years, BMI ≤ 25 g/m2, and hemoglobin level ≤ 12 g/dL and initial presentation with NSTEMI. Conclusions: In our study, number of revascularizations and survival was similar between cancer patients with CAD treated with BMS and DES. These finding suggests that DES use is not associated with increased risk for stent thrombosis and as cancer survival improves, there is more role for DES.